2014
DOI: 10.1139/cjpp-2014-0022
|View full text |Cite
|
Sign up to set email alerts
|

Monoammonium glycyrrhizate suppresses tumor necrosis factor-α induced chemokine production in HMEC-1 cells, possibly by blocking the translocation of nuclear factor-κB into the nucleus

Abstract: Monoammonim glycyrrhizate (MAG) derived from licorice has been shown to have anti-inflammatory properties. Chemokines are vital inflammatory mediators that are involved with endothelial damage from leukocyte infiltrates in various inflammatory skin diseases. In this study, we investigated the anti-inflammatory effects and mechanisms of MAG on tumor necrosis factor-α (TNF-α) induced chemokine production in a human dermal microvascular endothelial cell line (HMEC-1). HMEC-1 cells were treated with TNF-α, with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Cimato et al (24) found that inflammatory cytokines, rather than cholesterol, regulated the expression of CX3CL1 in atherosclerosis. Cao et al suggested that human dermal microvascular endothelial cell-1 in patients with inflammatory skin disease induced chemokines, including CXCL8, CX3CL1 and CXCL16, by activating the NF-κB signaling pathway when stimulated by TNF-α, which is in agreement with our previous finding that LPS-NF-κB-CX3CL1 exists in human bronchial epithelial cells (5,25). The present study revealed that CX3CL1-shRNA inhibited the secretion of NF-κB in the thrombus-stimulated LMVEC model, which was also consistent with a previous report (26).…”
Section: Discussionsupporting
confidence: 92%
“…Cimato et al (24) found that inflammatory cytokines, rather than cholesterol, regulated the expression of CX3CL1 in atherosclerosis. Cao et al suggested that human dermal microvascular endothelial cell-1 in patients with inflammatory skin disease induced chemokines, including CXCL8, CX3CL1 and CXCL16, by activating the NF-κB signaling pathway when stimulated by TNF-α, which is in agreement with our previous finding that LPS-NF-κB-CX3CL1 exists in human bronchial epithelial cells (5,25). The present study revealed that CX3CL1-shRNA inhibited the secretion of NF-κB in the thrombus-stimulated LMVEC model, which was also consistent with a previous report (26).…”
Section: Discussionsupporting
confidence: 92%
“…Glycyrrhizin has been confirmed to have both anti-inflammatory and anti-viral influences by combining directly to HMGB1, and inhibits its chemoattractant and mitogenic activities ( 15 ). Our previous study found that glycyrrhizin suppresses TNF- α induced chemokine production in HMEC-1 cells ( 16 ). We also found that the serum HMGB1 level of 16 Henoch– Schonlein purpura patients was significantly lower after treatment with glycyrrhizin ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that DPMCs and macrophages can stimulate angiogenesis through potent pro-angiogenic factors, and secretory DPMCs, macrophages and T cells have also been noted to affect adjacent non-endothelial cells or to recruit each other via chemotactic signals, and these potential factors jointly maintain the stability of the skin microenvironment ( 34 , 35 ).Marvelous ultrastructural changes appeared during xenobiotics attack. Pericytes underwent tighter junctions with DMECs but did not generate the pathological changes of gap formation ( 9 , 10 , 36 40 ). We tend to identify it as a physiological change caused by altered local permeability pressure after needle-free injection, since pericytes play an important role in regulating microvascular permeability, which would permit more hemolymph exchange to proceed ( 41 ).…”
Section: Discussionmentioning
confidence: 96%
“…Ultrastructural evidences suggest that the center of DMUs is composed of DMECs that originate from the horizontal papillary plexuses ( 6 ). These structures are responsible for the blood supply to the dermis stratum papillare and are responsive to injury ( 7 ), hypoxia ( 8 ), and stress ( 9 , 10 ), which manifests in the ultrastructure by gap formation and altered deposition in the basement membrane material of the vascular wall ( 11 13 ). Pericytes are located adjacent to or above endothelial cell junctions, which can control the contraction of DMECs by upregulating endothelin-1 (ET-1) and downregulating of iNOS expressed by DMECs ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%